Extracellular cathepsin L stimulates axonal growth in neurons. (December 2017) - Tohda, Chihiro; Tohda, Michihisa
Abstract Objective Cathepsin L, a lysosomal endopeptidase expressed in most eukaryotic cells, is a member of the papain-like family of cysteine proteases. Although commonly recognized as a lysosomal protease, cathepsin L is also secreted and involved in the degradation of extracellular matrix proteins. Previous studies demonstrated that the secretion of cathepsin L was stimulated by basic fibroblast growth factor (bFGF) and bFGF-enhanced axonal terminal sprouting of motor neurons. Based on these results, although it has never been directly investigated, we hypothesized that extracellular cathepsin L may induce axonal growth. Results To confirm the hypothesis, the axonal growth activity of recombinant cathepsin L was evaluated in cultured cortical and spinal cord neurons. Treatment with recombinant cathepsin L significantly enhanced axonal growth, but not dendritic growth. This result indicated that extracellular cathepsin L may act as a new neuronal network modulator.